Efficacy of argentine propolis formulation for topical treatment of canine otitis externa - Lozina, Laura Analía (2010)
The therapeutic effects of Argentine propolis ear drop formulation on canine otitis externa were evaluated. Forty-eight dogs with symptoms of otitis externa were randomly assigned to double-blinded, controlled clinical trial to evaluate the efficacy of topical formulation with propolis versus a topical placebo in the treatment of otitis externa. The propolis preparation and placebo were administrated into both external ear canals, twice daily for 14 days. Throughout the study, clinical examination and microbiological analysis of dogs ear exudates were made. The most frequent microorganisms isolated in culture media were: Malassezia pachydermatis (54.2%), Staphylococcus aureus (43.8%), coagulase-negative Staphylococcus (25.0%), Pseudomonas aeruginosa (20.8%), Candida albicans (18.8%), Proteus mirabilis (16.7%), Streptococcus spp. (16.7%), Enteroccocus faecalis (12.5%), Escherichia coli (12.5%), Staphylococcus intermedius (6.3%), Klebsiella spp. (4.2%), and Candida glabrata (2.1%). Whereas the control group did not recover from the infectious ear disease, the propolis preparation exhibited antimicrobial activity against most of the microorganisms isolated from samples of the treated group. In addition, no propolis-adverse effects were observed. This allowed propolis-treated patients to show a significant improvement of the clinical parameters. Thus, this new Argentine propolis ear drop formulation may be used for topical treatment of otitis externa in dogs.